2019
DOI: 10.1186/s12877-019-1382-x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence, risk factors and prognostic implications of dysphagia in elderly patients undergoing hip fracture surgery in Korea

Abstract: BackgroundDysphagia is prevalent in geriatric patients, such as elderly hip fracture patients, and is associated with a poor prognosis. This study investigated (1) the prevalence of dysphagia based on clinical screening and a video-fluoroscopic swallowing study (VFSS), (2) the risk factors of dysphagia, and (3) the prognostic implications of dysphagia in elderly patients (≥ 65 years) undergoing hip fracture surgery.MethodsIn this retrospective study, data from 393 female and 153 male patients ≥65 years of age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 36 publications
(48 reference statements)
1
17
1
11
Order By: Relevance
“…In this study, the prevalence of dysphagia after the surgery was 12.3%, which slightly increased to 13.4% at discharge. Previous reports showed the prevalence of dysphagia as 5.3~44% after hip fracture [14][15][16][17]. The difference in the results between those previous studies and ours may be explained by the difference in the diagnosis of dysphagia and the patient characteristics.…”
Section: Discussioncontrasting
confidence: 84%
See 4 more Smart Citations
“…In this study, the prevalence of dysphagia after the surgery was 12.3%, which slightly increased to 13.4% at discharge. Previous reports showed the prevalence of dysphagia as 5.3~44% after hip fracture [14][15][16][17]. The difference in the results between those previous studies and ours may be explained by the difference in the diagnosis of dysphagia and the patient characteristics.…”
Section: Discussioncontrasting
confidence: 84%
“…Therefore, it can be inferred that older people with sarcopenia and severely low SMI and hand-grip strength are at higher risk of developing dysphagia after hip fracture surgery. Previous studies indicated that the risk factors for dysphagia in older patients with hip fracture were low serum albumin level, female gender, mental disorientation following surgery, and reduced physical status (ASA III and IV) [14][15][16][17]. Low serum albumin was associated with sarcopenia [13,27].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations